2016
DOI: 10.1038/srep33025
|View full text |Cite
|
Sign up to set email alerts
|

Light effect on Click reaction: Role of photonic quantum dot catalyst

Abstract: Due to the light excitation, the valence band electron of the copper (I) sulfide quantum dot transfer to the conduction band and act as a scavenger of the terminal proton of the alkyne in the presence of organic azide with the formation of 1,4-disubstituted 1,2,3-triazoles, where the copper(I) species of Cu2S act as a catalyst for the reaction. The above cycloaddition reaction between alkyne and azide is commonly known as the Click reaction. In this study, experiments were carried out under the exposure of ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…In the spectrum (b), a characteristic peak at 1027 cm −1 represents the vibration of ‐C‐O‐C‐ in MPEG‐doped Cu (I)‐polyaniline. The detailed characterization of the Cu (I)‐polyaniline system is available elsewhere …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the spectrum (b), a characteristic peak at 1027 cm −1 represents the vibration of ‐C‐O‐C‐ in MPEG‐doped Cu (I)‐polyaniline. The detailed characterization of the Cu (I)‐polyaniline system is available elsewhere …”
Section: Resultsmentioning
confidence: 99%
“…Copper serves as a catalyst for the title reaction, whereas MPEG scavenges the free‐radicals with the formation of stable carbon‐centered free‐radicals that abstract the H‐atom from the alkyne molecule by means of a hydrogen atom transfer mechanism, and finally proceed for the triazole product in the presence of an azide molecule. In association with our ongoing research on the fabrication of effective catalysts for the cyclo‐addition of azide and alkyne molecules, further efforts will undertake in future for the development of new materials as catalyst to perform the similar kind of reactions by involving the heterocycle substituted azide molecules.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Luz et al showed Copper catalyzed ‘click’ reaction by benzyl azide as substrate . Nandi and co‐workers also showed the Copper catalyzed ‘click’ reaction . Besides, the synthesis of β‐hydroxy‐1,2,3‐triazoles has also been performed through ‘click’ reaction by the use of suitable epoxides with CuSO 4 or CuI .…”
Section: Introductionmentioning
confidence: 99%